INTERNALIZATION OF CHILDREN'S INDEPENDENCE VALUE; MANAGEMENT OF ORIENTATION AND MOBILITY PROGRAMS FOR CHILDREN WITH BLIND - Eti Suhaeti; Sofyan Sauri; Mupid Hidayat; Sunardi Sunardi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
The issue that schools, parents, and the community still lacks attention to the independence of blind children and even stereotypes of blind children who are considered to be dependent on others for their whole life becomes the basis for this research. This study aims to obtain an empirical picture of the internalization of the value of independence through orientation and mobility programs for blind children at extraordinary school. This research uses a qualitative with case study. Researchers used interviews, observations, and documentation to obtain accurate and accountable information. The data analysis technique is carried out in stages, including data reduction, presentation, and conclusion. The results showed that the internalization of the value of independence through orientation and mobility programs for blind children began with planning, implementing, and evaluating the program's success. This research has implications for the importance of strengthening the value of students' independence through innovative and superior programs arranged in a planned and systematic manner so that the desired goals can be achieved optimally.